Achieving highly efficient narrowband sky-blue electroluminescence with alleviated efficiency roll-off by molecular-structure regulation and device-configuration optimization. Issue 41 (27th September 2022) - Yan, Xianju; Li, Zhiqiang; Wang, Qingyang; Qu, Yupei; Xu, Yincai; Wang, Yue
Abstract : B–N-containing emitter based MR-TADF OLEDs exhibiting a narrowband sky-blue emission with the FWHM of 29 nm, the maximum EQE of 31.0% and low efficiency roll-off were achieved by molecular regulation and device optimization. Abstract : Multiple resonance effect induced thermally activated delayed fluorescence (MR-TADF) materials that can exhibit high luminous efficiency and color purity have aroused tremendous attention owing to their promising applications in wide color gamut displays. However, organic light-emitting diodes (OLEDs) based on MR-TADF emitters generally suffer from severe efficiency roll-off in a high brightness circumstance, which is disadvantageous to their practical application. Herein, to reduce the efficiency roll-offs of MR-TADF OLEDs, we systematically conceive how to regulate the molecular structure and optimize the device configuration. On the one hand, the addition of sterically hindered groups to the periphery of the primitive MR framework facilitates the weakening of contact between neighboring molecules, which reduces the occurrence of bimolecular events involving triplet excitons. On the other hand, the TADF or iridium-complex sensitizing device structures provide an assisted energy transfer channel from a sensitizer to a MR-TADF emitter, which suppresses the redundant excited state energy consumption pathways. As a result, the t DPA-DtCzB-based OLED exhibits a narrowband sky-blue emission with the full-width at half-maximum (FWHM) of 29 nm, the maximum external quantum efficiency (EQE) of 31.0%, and a high EQE of 23.3% at the practical high luminance of 1000 cd m −2 . These excellent device performances of the emitter render it an attractive candidate for wide color gamut displays.